Human blood vessel microbiota in healthy adults based on common femoral arteries of brain-dead multi-organ donors - Hidi, László; Kovács, Gergely Imre; Szabó, Dóra; Makra, Nóra; Pénzes, Kinga; Juhász, János; Sótonyi, Péter; Ostorházi, Eszter (Frontiers in Cellular and Infection Microbiology, 2022)
Discovery of human microbiota is fundamentally changing our perceptions of certain diseases and their treatments. However little is known about the human blood vessel microbiota, it may have important effects on vascular pathological lesions and vascular homograft failure. In our prospective survey study fourteen femoral arteries, harvested from donors in multi-organ donations, were examined using the V3-V4 region 16S rRNA sequencing method. The most abundant phyla in the human vascular microbiota were Proteobacteria, Firmicutes and Actinobacteria. At the genus level, the most abundant taxa were Staphylococcus, Corynebacterium, Pseudomonas, Bacillus, Acinetobacter and Propionibacterium. Of the bacterial taxa that have an indirect effect on the development of atherosclerosis, we found Porphyromonas gingivalis, Prevotella nigrescens and Enterobacteriaceae spp. with different abundances in our samples. Of the bacteria that are more common in the intestinal flora of healthy than of atherosclerosis patients, Roseburia and Ruminococcus occurred in the majority of samples. The human arterial wall has a unique microbiota that is significantly different in composition from that of other areas of the body. Our present study provides a basis for ensuing research that investigates the direct role of the microbiota in vascular wall abnormalities and the success of vascular allograft transplantations.